The role of dental anxiety in shaping patient satisfaction with dental services among patients visiting a tertiary care hospital: a cross-sectional study - Tirpude, Taniya N.; Warhekar, Shilpa A.; Kokane, Noopur B.; Khatri, Sachin G.; Dhote, Aniket V.; Jathar, Astha A. (International Journal Of Community Medicine And Public Health, 2025)
Background: The study aimed to examine the effect of dental anxiety on patient satisfaction with dental services and whether dental anxiety influences satisfaction levels among patients visiting tertiary care hospitals. Methods: The method was conducted among 356 dental patients at a tertiary care hospital, Nagpur. The Modified Dental Anxiety Scale (MDAS) was used to assess anxiety levels in patients. A pre-validated questionnaire was used to measure patient satisfaction with dental services. Results: Respondents were generally satisfied, although some internal differences were observed. Of the 356 responses, 92.1% of participants reported being satisfied, while 7.9% were unsatisfied. Satisfaction level was higher among younger age groups, though this association was not statistically significant. Males reported greater satisfaction (53.4%) compared to females (46.6%). No significant association was found between satisfaction and education level. However, satisfaction was highest among patients with education levels below graduates. Dental anxiety was more prevalent in younger patients. Females experienced higher dental anxiety (18.9%) than males (7.5%). The highest levels of dental anxiety were observed among those with education below graduation. Conclusions: Patients with higher dental anxiety reported lower satisfaction. Respondents were generally satisfied with dental services, except for waiting times. Older patients were less satisfied compared to younger ones. Males were more satisfied than Females.